Coagulation Factor Xa and Protease-Activated Receptor 2 as Novel Therapeutic Targets for Diabetic Nephropathy - Oe, Yuji; Hayashi, Sakiko; Fushima, Tomofumi; Sato, Emiko; Kisu, Kiyomi; Sato, Hiroshi; Ito, Sadayoshi; Takahashi, Nobuyuki (Arteriosclerosis, thrombosis, and vascular biology, 2016)
OBJECTIVE—The role of hypercoagulability in the pathogenesis of diabetic nephropathy (DN) remains elusive. We recently reported the increased infiltration of macrophages expressing tissue factor in diabetic kidney glomeruli; tissue factor activates coagulation factor X (FX) to FXa, which in turn stimulates protease-activated receptor 2 (PAR2) and causes inflammation. APPROACH AND RESULTS—Here, we demonstrated that diabetes mellitus increased renal FX mRNA, urinary FXa activity, and FX expression in glomerular macrophages. Administration of an oral FXa inhibitor, edoxaban, ameliorated DN with concomitant reductions in the expression of PARs (Par1 and Par2) and of proinflammatory and profibrotic genes. Diabetes mellitus induced PAR2, and lack of Par2 ameliorated DN. FXa or PAR2 agonist increased inflammatory cytokines in endothelial cells and podocytes in vitro. CONCLUSIONS—We conclude that enhanced FXa and PAR2 exacerbate DN and that both are promising targets for preventing DN. Alleviating inflammation is probably more important than inhibiting coagulation per se when treating kidney diseases using anticoagulants.